Primiparous women's knowledge and satisfaction based on their attendance at childbirth preparation classes - Robab Hassanzadeh; Fatemeh Abbas‐Alizadeh; Shahla Meedya; Sakineh Mohammad‐Alizadeh‐Charandabi; Mojgan Mirghafourvand (Wiley, 2021)
Abstract Aim To compare primiparous women's childbirth knowledge and their satisfaction with the childbirth preparation classes between regular and irregular attenders. Design A cross‐sectional study. Method This study was conducted on 136 primiparous pregnant women attending health centres in Tabriz, Iran. Women's knowledge on childbirth and their satisfaction with childbirth preparation classes were measured by using reliable tools via interviews. An independent t test was applied to compare women's knowledge and satisfaction scores between regular and irregular attenders. Results The mean score of knowledge was significantly higher among women who were regular attenders compared to irregular attenders (p < .001). Although there were no significant differences in total satisfaction score between the women (p = .342), women with regular attendance reported that childbirth preparation classes reduced their anxiety about labour. Conclusions Regular attendance at childbirth preparation classes is associated with higher women's knowledge and lower feelings of anxiety regarding labour and birth.